Frequency and diagnostic significance of anti-cyclic citrullinated peptide antibodies (ACCP) and anti-modified citrullinated vimentin antibodies (AMCV) in children with early juvenile arthritis - S O Salugina (Научно-практическая ревматология, 2008)
Objective. To determine frequency of anti-cyclic citrullinated peptide antibodies (ACCP) and anti-modified citrullinated vimentin antibodies (AMCV) elevation and their diagnostic significance in children with early juvenile arthritis (JA). Material and methods. ACCP were evaluated in serum of 80 pts with early JA (36 girls, 44 boys, mean age 8,5±5,03 years), AMCV — in 85 pts with early JA (49 girls and 36 boys) aged from 1,5 to 16 years (mean age 8,7±4,9 years). Disease duration in all children was less than 6 months. Control group included 54 grown up pts with early rheumatoid arthritis (RA), 27 - with undifferentiated arthritis (UDA) and 37 conditionally healthy children. АССР was assessed by immuno-enzyme assay (IEA) with commercial kits “Axis Shield Diagnostics" (Great Britain), upper normal limit 5,0 U/ml. AMCV was examined by IEA with commercial kits “Orgentec Diagnostics” (Germany), upper normal limit — 25 U/ml. Results. ACCP was elevated in 7 children with early JA (8,8%). Frequency was higher than in healthy children but lower than in grown up pts with early RA and comparable with UDA. In juvenile rheumatoid arthritis (JRA) ACCP were more frequent than in juvenile chronic arthritis (JCA). Concentration was higher in rheumatoid factor (RF) positive pts with polyarticular JA. AMCV level was elevated in in 23 (27,1%) pts with early JA (more frequent than in healthy donors but less frequent than in grown up pts with early RA and UDA). AMCV was significantly more frequent in JRA than in JCA and in RF positive than in RF negative pts. AMCV concentration in JA was higher than in healthy children but lower than in grown up pts with RA. It was also higher in RF+ than RF- JA. ACCP and AMCV correlated with swollen joint count, tender joint count and RF. AMCV also correlated with ESR and CRP. Conclusion. In pts with early JA ACCP and AMCV are equally or more frequent than RF. In spite of low sensitivity they have high specificity for JRA in contrast to JCA. Assessment of ACCP itself or in combination with RF and AMCV is of significant importance for prognosis of polyarticular joint damage with risk of significant functional disability development and timely administration of proper quite often aggressive therapy in early stage of the disease.